First record of Epidendrum ×doroteae (Orchidaceae) in South America - da Silva, David F.; do Nascimento, Erlediel G.; Barberena, Felipe F. V. A. (Nature Conservation Research: Заповедная наука, 2024)
Epidendrum ×doroteae (Orchidaceae), a natural hybrid between Epidendrum ciliare and Epidendrum nocturnum, was hitherto known only from a few specimens collected during the 1940s–1990s in Honduras, Central America. Epidendrum ×doroteae is recorded here for the first time in Nicaragua and in South America, in Brazil. We found three clusters of individuals of the hybrid in sympatry with the parental species on Marajó Island, state of Pará, in the Brazilian Amazon, and we recognised two specimens from Nicaragua deposited in the herbaria AMO and MO as E. ×doroteae. Epidendrum ×doroteae and the parental taxa have star-shape flowers with yellowish-green sepals and petals. However, E. ×doroteae differs from the parental species when fertile by the lateral lobes of the lip, which have an irregularly serrate-dentate, rarely slightly fimbriate margin vs. entire to slightly undulate margin in E. nocturnum and distinctly fimbriate margin in E. ciliare.